2013
DOI: 10.5114/ms.2013.39976
|View full text |Cite
|
Sign up to set email alerts
|

The effect of functional status of the ovaries on the embryological results of controlled ovarian hyperstimulation

Abstract: Introduction: Controlled ovarian hyperstimulation is an integral part of infertility treatment. Despite many years of use, some aspects of controlled ovarian stimulation have not yet been clarified, especially the role of the functional status of the ovaries before hormonal stimulation. Aim of the research: To assess the effect of the functional status of the ovaries on the embryological results of controlled ovarian hyperstimulation. Material and methods: The retrospective study included female patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…Previous research has demonstrated that dysmenorrhea is a complex process that depends on various factors [1][2][3]. Both our study and research conducted by other authors have shown that the following factors may have an impact on the development of dysmenorrhea: genetic causes, including the condition diagnosed in the mother and sisters, premenstrual syndrome (PMS), early age of menarche, stressful lifestyle, the lack of physical activity, loss of weight, unhealthy habits, social problems, depression, and even low self-esteem [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated that dysmenorrhea is a complex process that depends on various factors [1][2][3]. Both our study and research conducted by other authors have shown that the following factors may have an impact on the development of dysmenorrhea: genetic causes, including the condition diagnosed in the mother and sisters, premenstrual syndrome (PMS), early age of menarche, stressful lifestyle, the lack of physical activity, loss of weight, unhealthy habits, social problems, depression, and even low self-esteem [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have demonstrated that hormones, particularly increased secretion of prostaglandins, may cause dysmenorrhea [3][4][5]. Prostaglandins lead to excessive contractile activity of the uterus, with the consequent hypoxia and pain [2]. In addition to prostaglandins, markers of inflammation and oxidative stress participate in the pathomechanism of dysmenorrhea [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the European Drug Administration (EMA) and the Food and Drug Administration (FDA) have advised that drugs can pose a highly toxic risk to the reproductive system [2]. The ovaries which produce eggs are an integral part of the female reproductive system [3]. The development of the ovaries during puberty needs many nutrients, growth factors and endocrine hormones [4].…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, peningkatan kadar vasopresin serum, oksida nitrat, dan interleukin-6 (IL-6) telah dilaporkan pada wanita dengan disminore primer (Sun et al, 2005), dan peningkatan peroksidasi lipid dan konsentrasi radikal bebas terjadi selama dismenore (Madamanchi et al, 2005). Peningkatan ini dibuktikan pada wanita dengan dismenore memiliki kadar PG yang lebih tinggi dalam plasma dan limbah menstruasi dibandingkan wanita tanpa dismenore (Mrugacz et al, 2013).…”
Section: Hasil Dan Pembahasanunclassified